2022
DOI: 10.1021/acsnano.1c07687
|View full text |Cite
|
Sign up to set email alerts
|

Opsonin-Deficient Nucleoproteic Corona Endows UnPEGylated Liposomes with Stealth Properties In Vivo

Abstract: For several decades, surface grafted polyethylene glycol (PEG) has been a go-to strategy for preserving the synthetic identity of liposomes in physiological milieu and preventing clearance by immune cells. However, the limited clinical translation of PEGylated liposomes is mainly due to the protein corona formation and the subsequent modification of liposomes’ synthetic identity, which affects their interactions with immune cells and blood residency. Here we exploit the electric charge of DNA to generate unPEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…to avoid the involving of opsonin proteins in the corona, guaranteeing the maintenance of the targeting efficiency of nanomedicines and the escape from the mononuclear phagocyte system [33]. Moreover, besides ligand and stealth polymer-based approach, recently the artificial protein corona has greatly emerged, namely by pre-coating the nanomaterials surface with antibodies or proteins to modulate the protein corona formation and induce an active cancer-targeting aimed at ensuring the specific therapeutic action of the system [34]. On the other hand, few studies have investigated how the altered interaction with the plasma membrane caused by the protein corona can influence the anticancer properties of nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to avoid the involving of opsonin proteins in the corona, guaranteeing the maintenance of the targeting efficiency of nanomedicines and the escape from the mononuclear phagocyte system [33]. Moreover, besides ligand and stealth polymer-based approach, recently the artificial protein corona has greatly emerged, namely by pre-coating the nanomaterials surface with antibodies or proteins to modulate the protein corona formation and induce an active cancer-targeting aimed at ensuring the specific therapeutic action of the system [34]. On the other hand, few studies have investigated how the altered interaction with the plasma membrane caused by the protein corona can influence the anticancer properties of nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Moreover, besides ligand and stealth polymer-based approach, recently the artificial protein corona has greatly emerged, namely by pre-coating the nanomaterials surface with antibodies or proteins to modulate the protein corona formation and induce an active cancer-targeting aimed at ensuring the specific therapeutic action of the system. 34 On the other hand, few studies have investigated how the altered interaction with the plasma membrane caused by the protein corona can influence the anticancer properties of nanomaterials. In this study, we used SK-BR-3 human breast cancer cells as model system of HER-2 positive cancer cells and GO as a model of HER-2 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Negative surface charge/ Artificial BC Reduced immune system recognition due to limited interaction with plasma membrane 60 Size increase/aggregation Immune clearance 42,60 Opsonins enrichment Phagocytosis 61,62 Protein conformational changes Inflammatory response triggering 63 , amyloid fibrils formation, autoimmunity 64,65 66 . More recently, the negative charge of DNA was exploited to produce a multilayered biomimetic NP type called "proteoDNAsome" whose negatively charged BC allows to elude the immune system more efficiently than PEGylated liposomes in vivo 67 .…”
Section: Bc Feature Effectmentioning
confidence: 99%
“…[ 13–14 ] To a similar end, a recent study revealed that the encasement with DNA species is helpful in attracting dysopsonin over opsonin. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[13][14] To a similar end, a recent study revealed that the encasement with DNA species is helpful in attracting dysopsonin over opsonin. [15] A next-level precision nanomedicine is expected to be one carrying dedicated protein corona that functionally fulfils goals beyond long circulation. Technically, coating with protein corona frequently evolved a one-time incubation of nanomaterials with specific fluid (plasma or serum).…”
Section: Introductionmentioning
confidence: 99%